Perancangan Board Game untuk Memfasilitasi Pembelajaran Mata Kuliah Pengantar Teknik Industri UK. Petra - Michelle Reyner; Nova Sepadyati; Karina Agustin (Jurnal Titra, 2020)
Board games are designed with the aim of facilitating the learning of Introduction to Industrial Engineering Courses in the UK. Petra to accommodate all student learning styles. The board game is gaming for education that is designed according to learning material in the Introduction to Industrial Engineering, questionnaire survey results and Learning Achievement of Graduates (CPL) 5 number 2, understanding the concepts and work systems to increase productivity. The method used for board game design is based on literature studies and surveys through questionnaires. The board game concept is about working/production systems in the company which consists of 4 processes, that is the process of purchasing raw materials, the production process, the quality checking process, and the sales process. Each process uses applied knowledge or material from the Introduction to Industrial Engineering courses such as Operations Research is a simple linear program, Work Design Analysis (APK) that is the learning curve, Quality Control (QC) which is the DMAIC concept (Define, Measure, Analyze, Improve, Control). That way board games can be an interesting and useful learning medium for students who are studying in the Introduction to Industrial Engineering course.